Method for preparing porous resin-based spherical activated carbon through one-step activation and carbonization and application of porous resin-based spherical activated carbon
Through a one-step carbonization activation method, the acid-base neutralization reaction absorption activator of the sulfonated resin in the alkaline solution was used to solve the problems of complex production processes of the existing activated carbon and uncontrollable pore size distribution, and the preparation of activated carbon with high specific surface area and pore volume was achieved, which was suitable for high-efficiency hydrogen adsorption.
Patent Information
- Application Number
- CN202311578915.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-21
- Filing Date
- 2023-11-23
- Publication Date
- 2025-03-21
AI Technical Summary
The preparation process steps of existing activated carbon are complicated and it is difficult to control the pore size distribution, resulting in low specific surface area and pore volume, which cannot meet the demand for efficient hydrogen adsorption at room temperature and low pressure.
The one-step carbonization activation method is used to immerse the sulfonated resin in an alkaline solution containing the activator, absorb the activator through acid-base neutralization, and carbonize and activate at high temperatures, and create pores simultaneously to increase the specific surface area of the activated carbon.
The process steps are simplified, the specific surface area and pore capacity of activated carbon are improved, and its hydrogen adsorption capacity is enhanced at room temperature and low pressure, which is suitable for the application of hydrogen storage materials.
Smart Images

Figure CN119660738A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a method and application for preparing porous resin-based spherical activated carbon by one-step activation carbonization, and belongs to the field of carbon materials. Background Art
[0002] With the continuous growth of global energy demand and the reduction of fossil fuel reserves, seeking alternative energy has become an important issue facing today's society. Hydrogen energy, as a clean and efficient form of energy, has attracted widespread attention from all over the world. The research on hydrogen storage technology is an important prerequisite for the large-scale application of hydrogen energy. Since the density of hydrogen at normal pressure and room temperature is very low, the storage and transportation costs are high, which limits the application and promotion of hydrogen energy. The research on hydrogen storage materials aims to find a method that can safely and efficiently store and release hydrogen, and to promote the development of hydrogen energy by taking hydrogen as an emerging industry of future sustainable energy. The main hydrogen storage methods now include high-pressure gaseous hydrogen storage, low-temperature liquid hydrogen storage and solid-state hydrogen storage, among which solid-state hydrogen storage has higher safety and lower cost, and is expected to be widely used. However, the relevant basic research on low-cost solid-state hydrogen storage materials is the core of breakthroughs in hydrogen storage and transportation, and the controllable preparation of low-cost and efficient hydrogen storage materials based on breakthroughs in hydrogen storage mechanisms is a top priority. Activated carbon is a porous carbon material with the characteristics of large specific surface area, high porosity and strong chemical stability after multiple high-temperature carbonization and activation treatments. In recent years, activated carbon has become one of the research hotspots of hydrogen storage materials due to its good chemical and physical properties. Compared with other hydrogen storage materials, the raw materials for carbon-based materials for hydrogen storage are widely sourced, including plants (wood, coconut shell, straw, etc.), minerals (coal, petroleum coke, asphalt, etc.) and polymer resins (polystyrene resin, phenolic resin, etc.). Activated carbon adsorption hydrogen storage has the advantages of light weight of storage containers, fast desorption, long cycle life and low cost. It is a very potential and competitive hydrogen storage material. High specific surface area activated carbon hydrogen storage is achieved by using the van der Waals force between its huge surface area and hydrogen molecules, which is a typical supercritical gas adsorption. On the one hand, the hydrogen absorption performance of activated carbon is closely related to the adsorption temperature and pressure. The lower the temperature and the greater the pressure, the greater the hydrogen storage capacity; on the other hand, the adsorption amount of H2 is related to parameters such as the specific surface area, pore size distribution and pore structure of the carbon material. Therefore, it is crucial to produce activated carbon with higher specific surface area, suitable pore size and other favorable factors for hydrogen adsorption. In order to achieve adsorption at lower pressure and room temperature, meet commercial standards, and at the same time meet the requirements of simple activated carbon production process, large-scale production and application, a lot of research is needed on raw materials and production processes. From the microscopic structure, the most fundamental factor that determines the quality of adsorption performance lies in its pore size distribution, especially the pore size (<2nm) and pore volume (>0.5mL / g) of the micropores, which are the core properties of carbon-based hydrogen storage materials. The activation technology of activated carbon is usually divided into physical activation and chemical activation according to the type of activator: physical activation usually refers to the activation process using gas activators, and commonly used gas activators mainly include water vapor, carbon dioxide, oxygen, air, etc.; chemical activation usually refers to the activation process using chemical activators, and commonly used chemical activators mainly include potassium hydroxide, zinc chloride, phosphoric acid, sulfuric acid, potassium carbonate, sodium hydroxide, phosphate esters, etc.
[0003] Physical activation methods usually require very high temperatures to complete activation, and the activation efficiency is not high, making it difficult to achieve a high specific surface area. Chemical activation methods are usually used to prepare activated carbon with a large specific surface area, but the existing activated carbon activation preparation process has complicated steps, requiring the pretreated carbon precursor to be carbonized into activated carbon, and then mixed with a large amount of activating agent for activation, and the pore size distribution of the generated activated carbon is uncontrollable; the specific surface area and pore volume of the activated carbon are low. Summary of the invention
[0004] In response to the above-mentioned problems existing in the carbonization and activation process of activated carbon in the prior art, the present application provides a method for preparing porous activated carbon by one-step carbonization and activation, wherein an acidic resin material is immersed in an alkaline solution containing an activator, and the activator is absorbed into the interior of the material through the adsorption capacity of the resin material and the acid-base neutralization effect. Under the action of high temperature, while the material is carbonized, the activator creates a large number of pores inside the material, thereby increasing the specific surface area of the activated carbon.
[0005] According to one aspect of the present application, a method for preparing porous resin-based spherical activated carbon by one-step activation carbonization is provided, comprising the following steps:
[0006] The sulfonated resin is immersed in an alkaline solution, dried, carbonized, acid-washed, and dried to obtain the porous resin-based spherical activated carbon.
[0007] The sulfonated resin can be fresh resin or waste resin. The method is simple, the amount of KOH used is small, the prepared spherical activated carbon has good fluidity, and the gaps between the particles facilitate the rapid diffusion of hydrogen between the materials.
[0008] Optionally, the sulfonated resin is selected from at least one of polystyrene resin, phenolic resin and epoxy resin;
[0009] Optionally, the content of sulfonate in the sulfonated resin is 4.5 to 10 mmol / g;
[0010] Optionally, the alkaline solution is selected from at least one of potassium hydroxide solution, sodium hydroxide solution, sodium bicarbonate, and potassium bicarbonate solution;
[0011] Optionally, the mass fraction of the alkaline solution is 10-50wt%.
[0012] Optionally, the solid-liquid ratio of the sulfonated resin to the alkaline solution is 1:1 to 1.5.
[0013] Optionally, the drying temperature is 80-150°C;
[0014] Optionally, the drying time is 1 to 12 hours.
[0015] Optionally, the carbonization temperature is 500-900°C;
[0016] Optionally, the carbonization time is 1 to 8 hours.
[0017] Optionally, the carbonization is performed under an inert atmosphere.
[0018] Optionally, the inert atmosphere is selected from at least one of nitrogen, argon and helium.
[0019] Optionally, the pickling conditions include: the pickling temperature is 20 to 60° C., and the pickling time is 2 to 24 hours.
[0020] Optionally, the acid used for pickling is at least one of hydrochloric acid, nitric acid and sulfuric acid.
[0021] Optionally, the mass fraction of the acid used in the pickling is 2 to 10 wt %.
[0022] Optionally, the drying conditions include: a drying temperature of 80 to 150° C. and a drying time of 2 to 8 hours.
[0023] According to another aspect of the present application, there is provided a porous resin-based spherical activated carbon prepared by the above method, wherein the content of micropores in the pore size of the porous resin-based spherical activated carbon is 50-70%;
[0024] The pore volume of the porous resin-based spherical activated carbon is 0.6 to 1.4 cm 3 ·g -1 ;
[0025] The specific surface area of the porous resin-based spherical activated carbon is 1700 to 2500 m 2 ·g -1 .
[0026] Optionally, the micropore specific surface area of the porous resin-based spherical activated carbon is 1350 to 2000 m 2 ·g -1 ;
[0027] The micropore volume of the porous resin-based spherical activated carbon is 0.5 to 0.8 cm 3 ·g -1 .
[0028] According to another aspect of the present application, there is also provided a use of the above-mentioned porous resin-based spherical activated carbon as a hydrogen storage material.
[0029] The beneficial effects of this application include:
[0030] 1) The method provided in this application is simple to operate, and can complete the preparation of porous resin-based spherical activated carbon in one step. A large number of pores are created inside the material, increasing the specific surface area of the activated carbon. In addition, the preparation process only requires one step of carbonization for simultaneous activation, omitting the separate pre-oxidation and activation steps in the prior art. The simplified process steps significantly reduce the production cost. The contribution and principle of the step of immersing the sulfonated resin in an alkaline solution to the one-step carbonization activation are as follows: the sulfonate groups in the sulfonated resin can react with the alkaline solution, allowing the activated components in the solution to quickly and evenly enter the resin. The spherical structure of the resin can be maintained during the carbonization and activation process, while creating pores on the surface and inside the resin.
[0031] 2) The porous resin-based spherical activated carbon prepared by the method provided in this application has a pore size mainly of micropores and a pore volume of 0.6 to 1.4 cm 3 ·g -1 The specific surface area is between 1700-2500m 2 ·g -1 between.
[0032] 3) The porous resin-based spherical activated carbon prepared by the method provided in this application has excellent hydrogen storage performance under 77K1MP conditions, with a mass hydrogen storage density between 2.09-3.22wt% and a volume hydrogen storage density between 10.57-11.47kg / m 3 between. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a schematic diagram of the porous resin-based spherical activated carbon hydrogen storage performance testing device applied for in this application.
[0034] Figure 2 This is an electron microscope image of the porous resin-based spherical activated carbon obtained in Example 1 of the present application, with a scale of 100 μm.
[0035] Figure 3 This is an electron microscope image of the porous resin-based spherical activated carbon obtained in Example 1 of the present application, with a scale of 1 μm. DETAILED DESCRIPTION
[0036] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0037] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0038] Example 1
[0039] Immerse an equal volume of 10g of sulfonated resin in an alkaline solution containing 50wt% potassium hydroxide, stir thoroughly to make it evenly impregnated, and then put it in an oven to dry at 120℃. Put the dried polystyrene resin into an atmosphere furnace, and heat it to 700℃ at 5℃ / min under a nitrogen atmosphere, and carbonize and activate it at a constant temperature for 2h. After cooling to room temperature, pickle it with 10wt% dilute hydrochloric acid at 60℃ for 4h under stirring, filter it, wash it with water until it is neutral, and dry it at 120℃ to obtain porous resin-based spherical activated carbon. The morphology electron microscope picture is as attached Figure 2 and attached Figure 3 As shown, it has a uniform micropore distribution.
[0040] Embodiment 2:
[0041] 10g of sulfonated resin was immersed in an alkaline solution containing 30wt% potassium hydroxide, stirred thoroughly to make it evenly immersed, and then placed in an oven for drying at 120°C. The dried polystyrene resin was placed in an atmosphere furnace, heated to 700°C at 5°C / min under a nitrogen atmosphere, and carbonized and activated at a constant temperature for 2h. After cooling to room temperature, it was acid-washed with 10wt% dilute hydrochloric acid at 60°C for 4h under stirring, filtered, washed with water until neutral, and dried at 120°C to obtain a porous resin-based spherical activated carbon. The micropore morphology was similar to that of Example 1.
[0042] Embodiment 3:
[0043] 10g of sulfonated resin was immersed in an alkaline solution containing 20wt% potassium hydroxide, stirred thoroughly to make it evenly immersed, and then placed in an oven for drying at 120°C. The dried polystyrene resin was placed in an atmosphere furnace, heated to 700°C at 5°C / min under a nitrogen atmosphere, and carbonized and activated at a constant temperature for 2h. After cooling to room temperature, it was acid-washed with 10wt% dilute hydrochloric acid at 60°C for 4h under stirring, filtered, washed with water until neutral, and dried at 120°C to obtain a porous resin-based spherical activated carbon. The micropore morphology was similar to that of Example 1.
[0044] Embodiment 4:
[0045] 10g of waste sulfonated resin was immersed in an alkaline solution containing 30wt% potassium hydroxide, stirred thoroughly to make it evenly immersed, and then placed in an oven for drying at 120°C. The dried polystyrene resin was placed in an atmosphere furnace, heated to 700°C at 5°C / min under a nitrogen atmosphere, and carbonized and activated at a constant temperature for 2h. After cooling to room temperature, it was acid-washed with 10wt% dilute hydrochloric acid at 60°C for 4h under stirring, filtered, washed with water until neutral, and dried at 120°C to obtain a porous resin-based spherical activated carbon. The micropore morphology was similar to that of Example 1.
[0046] Embodiment 5:
[0047] 10g of sulfonated resin was immersed in an alkaline solution containing 30wt% potassium hydroxide, stirred thoroughly to make it evenly immersed, and then placed in an oven for drying at 120°C. The dried polystyrene resin was placed in an atmosphere furnace, heated to 750°C at 5°C / min under a nitrogen atmosphere, and carbonized and activated at a constant temperature for 2h. After cooling to room temperature, it was acid-washed with 10wt% dilute hydrochloric acid at 60°C for 4h under stirring, filtered, washed with water until neutral, and dried at 120°C to obtain a porous resin-based spherical activated carbon. The micropore morphology was similar to that of Example 1.
[0048] Embodiment 6:
[0049] 10g of sulfonated resin was immersed in an alkaline solution containing 30wt% potassium hydroxide, stirred thoroughly to make it evenly immersed, and then placed in an oven for drying at 120°C. The dried polystyrene resin was placed in an atmosphere furnace, heated to 800°C at 5°C / min under a nitrogen atmosphere, and carbonized and activated at a constant temperature for 2h. After cooling to room temperature, it was acid-washed with 10wt% dilute hydrochloric acid at 60°C for 4h under stirring, filtered, washed with water until neutral, and dried at 120°C to obtain a porous resin-based spherical activated carbon. The micropore morphology was similar to that of Example 1.
[0050] Comparative Example 1:
[0051] Put 10g of sulfonated resin into an atmosphere furnace, heat it to 700℃ at 5℃ / min in a nitrogen atmosphere, carbonize it at a constant temperature for 2h, cool it to room temperature, immerse an equal volume of carbonized resin carbon in an alkaline solution containing 50wt% potassium hydroxide, stir it thoroughly to make it evenly impregnated, and then put it into an oven to dry at 120℃. (After drying, it will form a hard block, which is very difficult to take out.) Put the dried resin carbon into an atmosphere furnace, heat it to 700℃ at 5℃ / min in a nitrogen atmosphere, activate it at a constant temperature for 2h, cool it to room temperature, pickle it with 10wt% dilute hydrochloric acid at 60℃ for 4h under stirring, filter it, wash it with water until it is neutral, and dry it at 120℃ to obtain porous resin-based spherical activated carbon.
[0052] Schematic diagram of hydrogen storage device Figure 1 As shown, similar to the principle of the physical adsorption instrument, this device simulates a possible application scenario in reality, simulates the rapid charging and discharging process of hydrogen, and explores the hydrogen storage performance of the material. At the beginning of the adsorption hydrogen storage test, a certain volume and mass of hydrogen storage material is loaded into the fixed bed, sealed and the system is evacuated to vacuum, and the fixed bed is immersed in a Dewar flask filled with liquid nitrogen. After the temperature is cooled to the liquid nitrogen temperature, the hydrogen gas flow rate is controlled by a gas flowmeter, and hydrogen is quickly filled into the fixed bed. When the pressure rises to 1MPa, the hydrogen storage ends, and the hydrogen adsorption amount is calculated to explore the hydrogen storage performance of the hydrogen storage material.
[0053] The activated carbons prepared in Examples 1 to 6 and Comparative Example 1 were dried and pretreated, and subjected to hydrogen storage adsorption tests and nitrogen physical adsorption characterization at 77k and 1MP pressure. The results are shown in Table 1.
[0054] Table 1
[0055]
[0056] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A method for preparing porous resin-based spherical activated carbon by one-step activation carbonization, characterized in that: The following steps are involved: The sulfonated resin is immersed in an alkaline solution, dried, carbonized, acid-washed, and dried to obtain the porous resin-based spherical activated carbon.
2. The method according to claim 1, characterized in that The sulfonated resin is selected from at least one of polystyrene resin, phenolic resin and epoxy resin; Preferably, the content of sulfonate in the sulfonated resin is 4.5 to 10 mmol / g; The alkaline solution is selected from at least one of potassium hydroxide solution, sodium hydroxide solution, sodium bicarbonate, and potassium bicarbonate solution; The mass fraction of the alkaline solution is 10-50 wt%.
3. The method according to claim 1, characterized in that The solid-to-liquid ratio of the sulfonated resin to the alkaline solution is 1:1 to 1.
5.
4. The method according to claim 1, characterized in that: The drying temperature is 80-150°C; The drying time is 1 to 12 hours.
5. The method according to claim 1, characterized in that: The carbonization temperature is 500-900°C; The carbonization time is 1 to 8 hours; The carbonization is performed under an inert atmosphere.
6. The method according to claim 1, characterized in that The pickling conditions include: the pickling temperature is 20 to 60° C., and the pickling time is 2 to 24 hours; Preferably, the acid used for pickling is at least one of hydrochloric acid, nitric acid and sulfuric acid; Preferably, the mass fraction of the acid used in the pickling is 2-10wt%.
7. The method according to claim 6, characterized in that The drying conditions include: a drying temperature of 80 to 150° C. and a drying time of 2 to 8 hours.
8. A porous resin-based spherical activated carbon prepared according to the method according to any one of claims 1 to 7, characterized in that: The content of micropores in the pore size of the porous resin-based spherical activated carbon is 50-70%; The pore volume of the porous resin-based spherical activated carbon is 0.6 to 1.4 cm 3 ·g -1 ; The specific surface area of the porous resin-based spherical activated carbon is 1700 to 2500 m 2 ·g -1 .
9. The porous resin-based spherical activated carbon according to claim 8, characterized in that: The micropore specific surface area of the porous resin-based spherical activated carbon is 1350 to 2000 m 2 ·g -1 ; The micropore volume of the porous resin-based spherical activated carbon is 0.5 to 0.8 cm 3 ·g -1 .
10. Use of the porous resin-based spherical activated carbon according to claim 8 or 9 as a hydrogen storage material.